2007
DOI: 10.1210/jc.2007-0147
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic T-Lymphocyte Associated Antigen 4 Gene Polymorphisms and Autoimmune Thyroid Disease: A Meta-Analysis

Abstract: The CT60 polymorphism of CTLA-4 maps an important genetic determinant for the risk of both GD and HT across diverse populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
129
5
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(154 citation statements)
references
References 59 publications
14
129
5
4
Order By: Relevance
“…In the available literature, studies on the polymorphism of CTLA4 exon1 A49G have shown conflicting results. Indeed, some studies disagree with our findings and suggest significant associations with GD and HT for both 49A/G and CT60G/A (Chistiakov and Turakulov 2003;Kavvoura et al 2007;Furugaki et al 2004) while others suggest that CTLA4 leads to the production of thyroid autoantibodies but it does not contribute to AITD (Tomer et al 2001).…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…In the available literature, studies on the polymorphism of CTLA4 exon1 A49G have shown conflicting results. Indeed, some studies disagree with our findings and suggest significant associations with GD and HT for both 49A/G and CT60G/A (Chistiakov and Turakulov 2003;Kavvoura et al 2007;Furugaki et al 2004) while others suggest that CTLA4 leads to the production of thyroid autoantibodies but it does not contribute to AITD (Tomer et al 2001).…”
Section: Discussioncontrasting
confidence: 81%
“…AITD are complex diseases in which susceptibility genes, mainly HLA genes, have been identified to initiate the autoimmune response against the thyroid gland in complex with environmental triggers (Kavvoura et al 2007). There are at least two hypotheses concerning the existence of an association between an allele and a disease: (1) the allele itself is the genetic variant causing an increased risk for the disease and (2) the allele itself is not causing the disease but rather a gene in linkage disequilibrium with it.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of CTLA-4 and HLA-DRB1 polymorphisms were reported previously. 32,33 Statistical analysis Allele frequencies were compared between groups by w 2 test on a 2 Â 2 contingency table using Statistica software package (StatSoft Inc., Tulsa, OK, USA). The genotype distribution was analyzed assuming three models of inheritance: dominant, codominant or recessive.…”
Section: Genotypingmentioning
confidence: 99%
“…10 CTLA4 encodes a co-stimulatory molecule of T cells, which is involved in the regulation of T-cell activation, 11,12 and it has been reported that the polymorphisms in exon 1 and 3¢-UTR region are associated with GD as well as Hashimoto thyroiditis, another autoimmune thyroid disease, in European and Asian populations. 10,[13][14][15] However, it is not clear how the CTLA4 and HLA polymorphisms would confer the risk to GD; that is, they operate independently or synergistically in determining the genetic risk. To clarify the issue, we analyzed a CTLA4 polymorphism (rs3087243, also called as CT60) in addition to HLA-A*02, DPB1*0202 and DPB1*0501 in association with GD.…”
Section: Introductionmentioning
confidence: 99%